KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS VII SMP ISLAM YLPI KOTA PEKANBARU - Ririn Riantika; Dudung Burhanudin; Auzar ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study discusses the students' reading comprehension class VII Islam YLPI city of Pekanbaru. This study also discusses reading and the things contained in the text itself as the key idea, the idea of descriptors, conclusions readings, and message / views of the authors. This study used a qualitative approach and methods of analysis that aims to give value to the aspects of the central idea, the idea of descriptors, conclusions readings, and message / views of the authors. Subject matter of this study is a test that uses objective tests. The results of this study are research data, analysis, and conclusions of the aspects of the central idea, the idea of descriptors, conclusions readings, and message / views of the authors.Keywords: Ability Reading Comprehension, Islamic junior high school students YLPI, descriptive discourse.